2017
DOI: 10.1002/bmc.4089
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of glaucocalyxin A and glaucocalyxin B in rat plasma by LC‐MS/MS and its application to a pharmacokinetic study after oral administration of Rabdosia japonica extract

Abstract: A specific and sensitive liquid chromatography tandem mass spectrometry (LC-MS/MS) method was developed and validated for the analysis of glaucocalyxin A and glaucocalyxin B in rat plasma using praeruptorin A as an internal standard. Separation was performed on a Hypurity C column (2.1 × 50 mm, 5 μm) with isocratic elution using 0.2% formic acid in water-acetonitrile (20:80, v/v). Mass spectrometric detection was conducted using selected reaction monitoring via an electrospray ionization source. Both analytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…14 The absorbance and elimination of GLA in rats were fast aer oral administration (T max ¼ 0.750 AE 0.224 h, t 1/2 ¼ 1.11 AE 0.17 h). 2 The excretion of GLA amounted to 23.8%, 12.8% and 35.68% in feces, urine, and bile within 12 h respectively. 15 These results indicated that GLA was fast metabolized and excreted mainly as metabolites.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…14 The absorbance and elimination of GLA in rats were fast aer oral administration (T max ¼ 0.750 AE 0.224 h, t 1/2 ¼ 1.11 AE 0.17 h). 2 The excretion of GLA amounted to 23.8%, 12.8% and 35.68% in feces, urine, and bile within 12 h respectively. 15 These results indicated that GLA was fast metabolized and excreted mainly as metabolites.…”
Section: Introductionmentioning
confidence: 94%
“…Rats in groups 5 & 6 were collected blood samples from the orbital vein of the rats with heparinized tubes at 0.25, 0.5, 0.75, 1, 2, 4, 8, 12 and 24 h aer dosing. 2 Then all the blood samples were immediately centrifuged at 4500 rpm for 10 min under 4 C to obtain plasma. The same biological sample was mixed and then stored at À80 C.…”
Section: Instrumentation and Analytical Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabdosia genus is an important genus of the Labiatae family, with about 150 species worldwide ( Huang et al, 2018 ). Rabdosia japonica (Burm.…”
Section: Introductionmentioning
confidence: 99%